P-Bar: Peanut-Based Snack Bar Innovation as Nutritious Food and Entrepreneurial Opportunity - Dewi Handayani; Triana Krisandini; Ayu Suci Lestari; Janisa Dwi Kurnia; Sefti Dahnia (Salus Publica: Journal of Community Service, 2026)
Indonesia has great potential in developing nutritious local foods, one of which is peanuts which are rich in protein and healthy fats. This study aims to develop